Reimagining Woman and Nature Beyond Dualism in Ann Jellicoe’s The Rising Generation - Gülter, Isıl Şahin (My University, 2022)
Ecofeminist philosophy has developed sophisticated critiques of the structures in western patriarchal culture that contribute to the continuing domination and oppression, not only of women but of nature as well. Drawing on ecofeminism’s critique of dualist structures as its principle guiding paradigm, this paper aims to explore how Ann Jellicoe comes to terms with the anti-dualist insights of ecological feminism in The Rising Generation (1969). The central issues that occupy and motivate ecofeminists, including the domination of women by men and humanity’s misappropriation of nature, are also Jellicoe’s primary concerns in the play. Jellicoe endeavors to depict characters and settings in a manner that rejects dualisms and embraces multiplicity, offering the basic conditions required for alternative representations of all the categories concerned, ‘woman,’ ‘man,’ ‘nature,’ and ‘culture’. In doing so, Jellicoe reconceptualizes the female/male and nature/culture relationships in configurations other than the traditional oppositions produced by the dualist strategy. In light of those preliminary observations, this paper indicates that in The Rising Generation, Jellicoe adopts an anti-dualist strategy to promote an egalitarian and pluralistic point of view through which all oppressive forms of domination within a culture can be unlocked.
Keywords: Nature; women; domination; dualism; British drama; ecofeminist literary criticism; Ann Jellicoe; The Rising Generation